Constructing efficient ɑ-Fe2O3/g-C3N4/HNTs-loaded heterojunction photocatalysts for photocatalytic oxidative desulfurization: Influencing factors, kinetics, and mechanism. (15th January 2023) - Zhou, Xiaoyu; Liu, Hang; Liu, Sixiao; zhang, Lei; Wang, Tianyi; Wang, Chengyin; Su, Dawei
Graphical abstract: Highlights: Highly efficient ɑ-Fe2 O3 /g-C3 N4 /HNTs photocatalysts were prepared. The conversion rate of dibenzothiophene was as high as 96.01 % in 3 h. The construction of Z-scheme heterojunctions promoted the photocatalytic activity. The mechanism of photocatalytic oxidative desulfurization was investigated. Abstract: The ɑ-Fe2 O3 /g-C3 N4 /HNTs (halloysite nanotubes) were prepared by a simple two-step calcination method. The HNTs skeleton increases the specific surface area of the material and enriches the adsorption reaction sites to prevent the reunion of g-C3 N4, while ɑ-Fe2 O3 further enhances the absorption in the visible region of g-C3 N4 . The transfer and separation of photogenerated carriers are promoted by the heterojunction structure constructed by ɑ-Fe2 O3 and g-C3 N4 . The results showed that dibenzothiophene in model oil could be converted by 96.01 % in 3 h under visible light irradiation using ɑ-Fe2 O3 /g-C3 N4 /HNTs-10 as the photocatalyst. The electron paramagnetic resonance spectrometry, radical capture experiments, and gas chromatography-mass spectrometry indicated that hydroxyl radicals, holes, and superoxide radicals were the main active substances of the photocatalytic system. Based on the above experimental analysis, the photocatalytic desulfurization mechanism of ɑ-Fe2 O3 /g-C3 N4 /HNTs composites was proposed. This work opens a new path for the development of novel and advanced clay-based photocatalytic materials.